XXVIIth general report on the activities of the European Communities 1993 - Commission of the European Communities (Brussels, Luxembourg : Commission of the European Communities, 1994)
This publication contains the twenty seventh general report on the activities of the European Communities.
Includes bibliographical references: p. 517-518.
gp 23/01/2019
Loans
Keywords: Law--European Economic Communities country; Law; Europe--European Economic Communities country; Belgium